The Last werewolf - Duncan, Glen, 1965- (New York : Alfred A. Knopf, 2011)
Jacob Marlowe has lost the will to live. For two hundred years he has wandered the world, enslaved by his lunatic appetites and tormented by the memory of his first and most monstrous crime. Now, the last of his kind, he contemplates suicide -- until a violent murder and an extraordinary meeting plunge him straight back into the desperate pursuit of life -- and love.
edited hb 2015-06-16
Keywords: Werewolves -- Fiction